SUNDERLAND, J. Gendered Discourses. Palgrave e Macmillan, 2004, 248 Págs. - Dias, Tatiana R. N. (Cadernos de Linguagem e Sociedade, 2010)
SUNDERLAND, J. Gendered Discourses. Palgrave e Macmillan, 2004, 248 Págs.